Synthesis, structure and electrochemical properties of a new cation ordered layered Li–Ni–Mg–Mo oxide. Issue 4 (19th January 2023) - Dong, Bo; Castells-Gil, Javier; Zhu, Pengcheng; Driscoll, Laura L.; Kendrick, Emma; Allan, Phoebe K.; Slater, Peter R.
Abstract : Disordered rocksalt Li1.2 Ni0.4 Ti0.4 O2 is transformed into a new cation ordered layered phase Li1.2 Ni0.4 Mo0.2 Mg0.2 O2 through a dual cation substitution strategy. Abstract : Lithium-rich oxides are attracting intense interest as the next generation cathode materials for lithium-ion batteries due to their high theoretical capacity. Nevertheless, these materials suffer from a number of shortcomings, such as oxygen loss at high voltage, large hysteresis and poor rate capability. In this work, we show that through a dual cation substitution strategy replacing Ti with Mo and Mg, the disordered rocksalt (DRS) Li1.2 Ni0.4 Ti0.4 O2 is transformed into a new cation ordered layered phase Li1.2 Ni0.4 Mo0.2 Mg0.2 O2, with the high valence dopant Mo 6+ on the (0, 0, 0) site. Li1.2 Ni0.4 Mo0.2 Mg0.2 O2 showed improved performance compared to that of the similarly prepared DRS Li1.2 Ni0.4 Ti0.4 O2 material (∼190 mA h g −1 vs . ∼105 mA h g −1 after 10 cycles, respectively). The characteristics of the electrochemical process were studied using ex situ XRD and XAS, which indicated the involvement of both Ni and Mo redox during the cycling as well as the electrochemical instability of the layered phase which changes to a disordered rocksalt phase on cycling.